Pericardial mass in a 71-year-old man. Issue 23 (21st July 2018) - Grazzini, Giulia; Calistri, Linda; Nardi, Cosimo
Abstract : Clinical introduction: A 71-year-old man, with a history of chronic aortic regurgitation and negative follow-up after bladder cancer resection 10 months before, had an aortic valve surgery. Two months after, a mass near the right side of the heart had been detected by transthoracic echocardiography performed for dyspnoea, without a cough or fever. The quality of ultrasound images did not allow for an appropriate evaluation due to the outcomes of the sternotomy and the presence of calcified pachypleurite. In order to evaluate this finding, coronary CT (CCT) (figure 1A, B ) and positron-emission tomography with 2-[18F] fluoro-2-deoxy-D-glucose (FDG-PET) (figure 1C ) were performed. Finally, a cardiac magnetic resonance (CMR) was requested (figure 1D–F, see online supplementary videos ). Question: Which of the following is the most likely diagnosis of the pericardial mass? Primary pericardial tumour. Pericardial metastasis. Intrapericardial abscess. Intrapericardial haematoma.